Presenting to Win : the Art of Telling Your Story - Weissman, Jerry (FT Press, 2008)
Named by FORTUNE Magazine as a "Must-Read" "Jerry Weissman makes the challenge of producing and delivering effective presentations delightfully simple. Read it and benefit!" Tim Koogle, Founding CEO, Yahoo! "A great read for all of us who have ever struggled with any aspect of our public speaking skills. Presenting to Win contains the same timeless techniques that helped me [18] years ago." Jeff Raikes, former President, Microsoft Business Division, Microsoft Corporation, and CEO, Bill and Melinda Gates Foundation "Jerry is The Man when it comes to making great pitches. If your pitch doesn't get a whole lot better after reading this book, something is wrong with you." Guy Kawasaki, Managing Director and Chairman, Garage Technology Ventures, and bestselling author of The Art of the Start "Presenting to Win is the shortest path to applause for any presenter. It will be your bible for the PowerPoint Age. It's loaded with easy actions and real examples that really work. I've used them. I know." Scott Cook, Founder, Intuit Thirty million presentations will be given today. Millions will fail. Millions more will be received with yawns. A rare few will establish the most profound connection, in which presenter and audience understand each other perfectly ... discover common ground ... and, together, decide to act. In this fully updated edition, Jerry Weissman, the world's #1 presentation consultant, shows how to connect with even the toughest, most high-level audiences ... and move them to action! He teaches presenters of all kinds how to dump those PowerPoint templates once and for all and tell compelling stories that focus on what's in it for the audience. Weissman's techniques have proven themselves with billions of dollars on the line. Thousands of his elite clients have already mastered them. Now it's your turn! What you must do to tell your story Focus before Flow: identifying your real goals and message The power of the WIIFY: What's In It For You Staying focused on what your audience really wants Capture your audience in 90 seconds ... and never let go! Opening Gambits and compelling linkages Master the art of online Web conferencing Connecting with your invisible audience From brainstorming through delivery Crafting the Power Presentation, one step at a time.